Pentingnya budaya kolaboratif : suatu tinjauan literatur - Yuni Kasmawati (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
At present, cooperation between organizations and within organizations is demanded that an organization be able to compete. In the educational environment, collaborative culture is considered as an important component in influencing overall school success. Based on a literature review, this article discusses the importance of collaborative culture in educational organizations as a strategy in increasing school effectiveness and increasing teacher capacity. This research shows that collaborative culture has an important role not only at the teacher and student level but also at the school level and ultimately will improve the quality of the school.